EMPIRICAL STUDIES IN DIDACTIC AUDIOVISUAL TRANSLATION - Plaza-Lara, Cristina ([S.l.] : ROUTLEDGE, 2024)
This collection showcases a wide range of empirical studies in didactic audiovisual translation (DAT), fostering replication of the present work to encourage future research and further expansion of DAT's applications in language learning settings. The book seeks to offer a complementary perspective with the spotlight on empirical work, building on previous lines of inquiry rooted in descriptive analysis and the experimental turn. The volume is divided into three parts, aiming to bring together disparate studies from a range of classroom contexts and educational levels which draw on a mixed-methods approach in one place. The first part features research on captioning, or written language transfer, while the second includes on studies on revoicing, or oral language transfer. A final section looks at combined studies integrating both revoicing and captioning, while looking ahead to possibilities for new lines of empirically grounded research on the use of audiovisual modes at the intersection of translation and foreign language education. This volume will be of interest to students and scholars in audiovisual translation, translation studies, language education, and technology and language learning.
Keywords: Language and languages -- Study and teaching; Audio-visual translation -- Study and teaching; LANGUAGE ARTS & DISCIPLINES / Translating & Interpreting